Cross-Cultural Perspectives on Corruption and Bribery: Sharia-Based Approaches to Anti-Corruption Law - Subari, Andi Akbar; Faisal, Achmad; Suprapto (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2026)
Background: Corruption and bribery are persistent global problems that undermine governance, economic growth, and societal trust. While numerous legal frameworks have been developed to address these issues, their effectiveness is often influenced by cultural, religious, and institutional contexts. In Muslim-majority countries, Sharia-based legal principles provide a distinctive ethical and normative foundation for combating corruption. Purpose: This study aims to examine cross-cultural variations in anti-corruption laws with a specific focus on the contributions of Sharia-based frameworks to ethical governance, transparency, and accountability. Methods: Employing a comparative legal analysis, the research reviews anti-corruption legislation, international conventions, and Islamic jurisprudence (fiqh) on integrity and public trust. Data are drawn from legal texts, case studies, and policy reports across multiple jurisdictions to evaluate enforcement mechanisms, preventive strategies, and public awareness campaigns. Findings: Employing a comparative legal analysis, the research reviews anti-corruption legislation, international conventions, and Islamic jurisprudence (fiqh) on integrity and public trust. Data are drawn from legal texts, case studies, and policy reports across multiple jurisdictions to evaluate enforcement mechanisms, preventive strategies, and public awareness campaigns. Theoretical and Practical Implications: The study contributes to legal anthropology and Islamic jurisprudence by framing anti-corruption laws within culturally rooted governance models. Practically, it offers policymakers strategies for integrating ethical-religious norms into legal reforms to improve transparency, strengthen institutions, and foster public trust. Originality/Novelty: systematically compare Sharia-based anti-corruption models with secular approaches through a cross-cultural lens, highlighting the role of religious-ethical frameworks as complementary tools to global legal standards